UPAYA ORGANIZATION FOR SECURITY AND CO-OPERATION IN EUROPE DALAM MEMBANTU MENANGANI KRISIS UKRAINA 2013-2014 - Alkurni Haskelindos; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This Paper will explain about how Organization for Security and Cooperation in Europe (OSCE) to help resolving Ukraine Crisis. OSCE as the biggest security organization in Europe has responsibility to help its participating states which have critical situation and domestic issues. In last November 2013, Ukraine Crisis has been begun after Yanukovich, the Ukraine President, rejected cooperation agreement with Europe Union (EU). After rejection of the agreement, demontstration from Ukraine mass was happened to protest the president policy at Ukraine Independent Square. This demontration is called “Maidan”, and day by day, demonstration became more intense. This protest also has impact to neighbor countries, like Russia. Russia action to respon this situation with military intervention to protect some people in east Ukraine who use Russia Language, this community indentified its self as Russian. Because of that, this crisis more likely ethnical conflict between Ukranian and Russian. This research used qualitative research method, with description analysis methods. Data collection techniques used are library research technique. Based on the data obtained by the researches that OSCE missions are peace movement, socializing democratic values, and open dialogue both for Ukraine government with Russia federation, and Ukraine government with its civilian. OSCE actions toward Ukraine Crissis are reporting specific situation on Ukriane to each participating states, observing president and parliamentary election, observing minority rights in east Ukraine, and open dialogue between related actors.Keywords: OSCE, Ukraine Crissis, Russia Intervention, OSCE actions, Ethnical Conflic